(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The present study aims to identify the private sector’s contribution to fixed capital formation in Iraq, as it is a highly important variable in the national economy. It provides an image of the investment plan of the country. It is also considered an indicator of the integrated economic plan that reflects productive capacities. The present study reveals that the private sector contributes little to fixed capital formation, amounting to (31.64%), compared to the public sector’s contribution of (68.35%). As for the stock of private fixed capital, its average is (21,888.65) billion dinars, and its productivity average is (4.509) billion dinars during the research period. One of the most important recommendations is to encourage the private sector to invest in economic sectors in order to develop the total private fixed capital formation for the purpose of increasing production by providing an appropriate legal and legislative environment and protecting and guaranteeing the rights of investors.